2020
DOI: 10.3390/vaccines8030498
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Adverse Events Caused by the Combined Use of Bevacizumab and Vascular Endothelial Growth Factor Receptor-Targeted Vaccination for Patients with a Malignant Glioma

Abstract: Anti-angiogenic therapy, targeting vascular endothelial growth factor (VEGF)-A/VEGF receptors (VEGFRs), is beneficial for tumor growth prevention in a malignant glioma. A simultaneous blockade using both bevacizumab (Bev), which targets circulating VEGF-A, and a multi-kinase inhibitor on VEGFRs was more effective for advanced solid cancers, including melanoma and renal cell carcinoma. However, previous clinical trials demonstrated a high adverse event rate. Additionally, no studies previously assessed treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, some studies have attempted to combine tumor vaccines with ICIs to maximize the benefits of immunotherapy. , For example, Wang et al loaded tumor antigens and anti-PD-L1 antibodies onto hollow mesoporous silica (HMS) to treat mice, demonstrating significant anticancer effects and a significant reduction in the required dosage compared to using ICIs alone. Similar to the results obtained in this study, we injected MC38 Mlh1 KD into mice to establish a syngeneic tumor model and found that treatment with TCL combined with anti-PD-L1 antibodies prolonged overall survival and prevented cancer progression compared to single immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have attempted to combine tumor vaccines with ICIs to maximize the benefits of immunotherapy. , For example, Wang et al loaded tumor antigens and anti-PD-L1 antibodies onto hollow mesoporous silica (HMS) to treat mice, demonstrating significant anticancer effects and a significant reduction in the required dosage compared to using ICIs alone. Similar to the results obtained in this study, we injected MC38 Mlh1 KD into mice to establish a syngeneic tumor model and found that treatment with TCL combined with anti-PD-L1 antibodies prolonged overall survival and prevented cancer progression compared to single immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] In the retrospective study, adverse event rates did not significantly differ between patients treated with Bev, those treated with vaccination, and those treated with Bev after vaccination. 35 This combined strategy may be an option in patients with NF2.…”
Section: Discussionmentioning
confidence: 99%
“…Xie H et al found bevacizumab combined with sorafenib as a salvage treatment for metastatic colorectal cancer patients who failed to various treatments (Xie et al 2020 ). At the same time, bevacizumab combined with multi-kinase inhibitors targeting VEGFRs has also been found to be equally more effective against advanced solid cancers, such as melanoma (Tamura et al 2020 ). Icotinib (a tyrosine kinase inhibitor that selectively targets EGFR) combined with bevacizumab has a stronger inhibitory effect on NSCLC growth in vivo than single target drugs without additional side effects (Jiang et al 2022 ).…”
Section: Drugs Targeting Vegfa In Cancer Therapymentioning
confidence: 99%